Simon Newcomb papers - Newcomb, Simon, 1835-1909.
Correspondence, diaries, speeches, writings, articles, reviews, commonplace books, financial records, genealogical material, charts, tables, computations, photographs, and other papers reflecting Newcomb's career in astronomy and mathematics, work as president of the Congress of Arts and Science in 1904, Saint Louis, Mo.; authorship of articles for encyclopedias and other publications; and personal and family affairs. Correspondents include Edward Emerson Barnard, Alexander Graham Bell, Lewis Boss, S.W. Burnham, William Wallace Campbell, James McKeen Cattell, George Davidson, Sir David Gill, Daniel Coit Gilman, Benjamin Apthorp Gould, George Ellery Hale, Asaph Hall, George William Hill, Edward Singleton Holden, S.P. Langley, Othniel Charles Marsh, Benjamin Peirce, Edward C. Pickering, T.J.J. See, Otto Struve, Charles D. Walcott, Carroll Davidson Wright, and Newcomb's wife, Mary Hassler Newcomb. Also includes correspondence with the Alvan Clark & Sons, Carnegie Institution of Washington, National Academy of Sciences (U.S.), Smithsonian Institution, and the periodical, Science.
Astronomer, mathematician, and economist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Barnard, Edward Emerson, -- 1857-1923 -- Correspondence; Bell, Alexander Graham, -- 1847-1922 -- Correspondence; Boss, Lewis, -- 1846-1912 -- Correspondence; Burnham, S. W. -- 1838-1921 -- Correspondence; Campbell, William Wallace, -- 1862- -- Correspondence; Cattell, James McKeen, -- 1860-1944 -- Correspondence; Davidson, George, -- 1825-1911 -- Correspondence; Gilman, Daniel Coit, -- 1831-1908 -- Correspondence; Gill, David, -- Sir, -- 1843-1914 -- Correspondence; Gould, Benjamin Apthorp, -- 1824-1896 -- Correspondence; Hale, George Ellery, -- 1868-1938 -- Correspondence; Hall, Asaph, -- 1829-1907 -- Correspondence; Hill, George William, -- 1838-1914 -- Correspondence; Holden, Edward Singleton, -- 1846-1914 -- Correspondence; Langley, S. P. -- 1834-1906 -- Correspondence; Marsh, Othniel Charles, -- 1831-1899 -- Correspondence; Newcomb, Mary Hassler -- 1840-1921 -- Correspondence; Peirce, Benjamin, -- 1809-1880 -- Correspondence; Pickering, Edward C. -- 1846-1919 -- Correspondence; See, T. J. J. -- 1866- -- Correspondence; Struve, Otto, -- 1819-1905 -- Correspondence; Walcott, Charles D. -- 1850-1927 -- Correspondence; Wright, Carroll Davidson, -- 1840-1909 -- Correspondence; Newcomb family; Alvan Clark & Sons -- Correspondence; Carnegie Institution of Washington -- Correspondence; National Academy of Sciences (U.S.) -- Correspondence; Smithsonian Institution -- Correspondence; Science -- Correspondence; Arts -- Congresses; Astronomy; Mathematics; Science -- Congresses; Astronomers; Economists; Mathematicians